2019
DOI: 10.18510/hssr.2019.75116
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Spending Leisure Time Among the College Students and Its Effects on Their Mental Health

Abstract: Purposes of the Study:Through the present study the investigators have tried to study the nature of activities of college-level students by which they were spending their leisure time. And to find out the effects of the nature of spending leisure time on the mental health of the students is another important purpose of the present study. Methodology:The investigators used the Descriptive Survey method for the present study. The Random sampling technique has been used for the selection of the sample. The invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
1
0
1
Order By: Relevance
“…Kemudian apabila meninjau jenis kegiatan nonakademik, penelitian ini menghasilkan temuan bahwa mahasiswa dengan kegiatan kategori lain-lain (berupa melakukan hobi dan berolahraga) memiliki skor rerata academic hardiness yang lebih tinggi daripada jenis kegiatan nonakademik lainnya. Kegiatan seperti menjalani hobi dan berolahraga termasuk ke dalam aktivitas leisure time (Das et al, 2019) yang dapat membantu mahasiswa mengelola stresnya. Leisure time juga membantu seseorang untuk dapat berpikir jernih dan memiliki jeda dari tuntutan, sehingga dapat menghadapinya dengan karakter yang positif, seperti meyakini bahwa dirinya mampu menghadapi tuntutan yang ada satu per satu dan meyakini bahwa tuntutan adalah tantangan (Qian et al, 2013).…”
Section: Pembahasanunclassified
“…Kemudian apabila meninjau jenis kegiatan nonakademik, penelitian ini menghasilkan temuan bahwa mahasiswa dengan kegiatan kategori lain-lain (berupa melakukan hobi dan berolahraga) memiliki skor rerata academic hardiness yang lebih tinggi daripada jenis kegiatan nonakademik lainnya. Kegiatan seperti menjalani hobi dan berolahraga termasuk ke dalam aktivitas leisure time (Das et al, 2019) yang dapat membantu mahasiswa mengelola stresnya. Leisure time juga membantu seseorang untuk dapat berpikir jernih dan memiliki jeda dari tuntutan, sehingga dapat menghadapinya dengan karakter yang positif, seperti meyakini bahwa dirinya mampu menghadapi tuntutan yang ada satu per satu dan meyakini bahwa tuntutan adalah tantangan (Qian et al, 2013).…”
Section: Pembahasanunclassified
“…Previous studies have found that psychosexual adjustment is linked to stress ( Arya et al, 2019 ), cancer and treatment ( Barnett et al, 2016 ; Rizzuto et al, 2021 ), puberty development ( Dwyer, 2020 ), leisure ( Williams et al, 2020 ), and personality ( Thompson et al, 2019 ; Hashemi, 2020 ), among which leisure is of great significance to everyone, especially college students who have plenty of free time ( Das and Barman, 2019 ). In addition, the role of individual personality on sexual psychology has also been of interest ( Frías et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%